Peningkatan keterampilan teknis penghuni panti melalui pelatihan instalasi listrik sederhana - Sabran F. Harun; Saharuddin R. Sokku; Purnamawati Purnamawati (Seminar Nasional Pengabdian Kepada Masyarakat, 2019)
Increasing the skills of the residents of theorphanage must always be carried out continuously. Thefactors underlying this include: the increase in the number oforphanages especially in big cities and so with residents whoneed a place to live. They come from various backgrounds.Funding for orphanages is still very hopeful for benefactorsand the local government. But the financing is not relied onsustainably and constantly. On the other hand, in general theresidents are in the productive age category, so it is verypossible for them to be able to finance themselves. Providingtechnical skills and building the spirit of entrepreneurship isone effort to reduce dependence on other parties. This wasdone by the UNM service team at the Miftahul Khairorphanage in Makassar City. The results obtained from thisactivity are assisted by the manager in preparing the future ofthe occupants. The skills of the participants increased insimple electricity installations. Besides that their desire forentrepreneurship began to emerge.